AN ANALYSIS OF THE DETERMINANTS AFFECTING THE PERFORMANCE OF MICROFINANCE INSTITUTIONS IN GHANA - ARTHUR-SAM, Jane (Journal of process management and new technologies, 2025)
Microfinance Institutions (MFIs) are crucial in providing services to the underprivileged, particularly those with limited incomes and the unorganized sector in a sustainable manner. In the Ghanaian business industry, these firms are primarily seen as vital institutions for progress against poverty and an excessive dependence on national and local governments. Thus, the goal of this study is to identify the factors affecting the performance of Microfinance institutions in Ghana. Multiple regression and descriptive statistics were used to analyze the secondary data gathered from the 133 MFIs in Ghana with SPSS. The study's conclusions showed that efficiency and liquidity have significantly positively impact on the firms' return on equity (ROE). Capital adequacy ratio (CAR) and non-performing loans (NPL) had no statistically significant effect on the Microfinance institutions' performance (ROE). Additionally, the study discovered a significant positive effect of CAR on the performance of the return on assets (ROA) on the MFIs. However, liquidity, efficiency and NPL had no statistical significant impact on the performance (ROA) of the companies. The research contributes to literature on the studies conducted on MFIs in Ghana and practically assists in improving and enhancing their performance. This study also promotes ways on how the government and stakeholders can support MFIs for a long-term sustainability and the economic growth in the country.